Pengaruh Diversifikasi Produk terhadap Profitabilitas dan Efisiensi Usaha Mikro di Sektor Perikanan - , Radhiana; , Sufitrayanti; Syamsuddin, Nurfiani; Rusmina, Cut; Kaifasyah, Teuku (Jurnal Serambi Engineering, 2025)
Product diversification is a crucial strategy for micro enterprises in the fisheries sector to enhance profitability, efficiency, and business sustainability. Heavy reliance on selling fresh fish often leads to unstable income among fishermen and fish processors due to price fluctuations and perishability risks. This study aims to analyze the impact of product diversification on the profitability and efficiency of micro-scale fisheries enterprises using a Systematic Literature Review (SLR) approach. The analysis was conducted by reviewing literature from international sources such as FAO, UNEP, UNIDO, and OECD, as well as empirical studies on innovation, operational efficiency, and fishery waste management. The findings indicate that product diversification can increase income by 20–40%, expand market reach, reduce raw material waste, and create a more efficient and environmentally friendly production system. Moreover, diversification generates significant socio-economic impacts, including new employment opportunities, enhanced skills among coastal communities, and improved competitiveness of local products in modern markets. However, the success of diversification largely depends on access to finance, technical skills, and market connectivity. Therefore, collaboration between entrepreneurs, government, cooperatives, and financial institutions is essential to achieve sustainable product diversification in the fisheries sector.